Impacts of urban sprawl in the Administrative Region of Ribeira tilde o Preto (Brazil) and measures to restore improved landscapes - Olivera, Lais Caroline Marianno de [UNESP]; Mendonca, Gislaine Costa de [UNESP]; Costa, Renata Cristina Araujo [UNESP]; Camargo, Regina Aparecida Leite de [UNESP]; Fernandes, Luis Filipe Sanches [UNESP]; Pacheco, Fernando Antonio Leal; Pissarra, Teresa Cristina Tarle [UNESP] (Elsevier B.V., 2023)
The present study addressed the problem of urban expansion in a large metropolis of Brazil (ARRP - Adminis-trative Region of Ribeira similar to o Preto), relating the evolution of urbanization in the past 35 years with losses of agricultural area and respective equivalent production and economic effects. Besides these food security and agribusiness issues, the study tracked important environmental consequences of the observed growing urbani-zation. This included water insecurity related with the occupation of watercourse networks, destruction of ri-parian vegetation that is legally protected as Permanent Preservation Areas (PPAs), and the occupation of Guarani Aquifer recharge areas with impermeable surfaces. The database consisted of Landsat images interpreted and processed in a Geographic Information System (GIS). The results indicate losses of rural area exceeding 350 km2 in the studied timeframe, with equivalent production and economic losses around 1.1 Mton/year and 230 MR$/year, on average. It is worth to mention the 40-75% overlap between the impermeable surfaces of some ARRP municipalities (e.g., Cajuru, Altin ' opolis) and recharge areas of Guarani Aquifer. The impermeable surfaces within the ARRP also affected approximately 7000 headwaters that were potential hotspots of shallow aquifer recharge. The urban sprawl destroyed more than 9100 km of natural watercourses and nearly 630 km2 of PPAs. The pathways recognized to improve the ARRP landscape included implementation of urban agriculture and landscape planning measures capable to protect the recharge to and the quality of Guarani Aquifer water, mostly anchored in the Municipal Director Plans, the prominent land use policy tools in the ARRP. This integrated, long-term, spatially explicit and quantitative assessment of urban sprawl impacts assembled with indications of landscape restoration policies and measures is novel in Brazil. On the other hand, studying the ARRP is worthwhile because of its historical relationship with the Brazilian ethanol program that brought an accelerated development to the region following the World oil crisis of 1970 s until now.
Keywords: Urbanization; Agricultural land reduction; Destruction of riparian vegetation; Reduced aquifer outcrops; Landscape planning; Land use policy